Hypervalent Iodine Reagents in Palladium-Catalyzed Oxidative Cross-Coupling Reactions - Shetgaonkar, Samata E.; Singh, Fateh V. (Frontiers in Chemistry, 2020)
Hypervalent iodine compounds are valuable and versatile reagents in synthetic organic chemistry, generating diverse array of useful organic molecules. Owing to their non-toxic and environment friendly features, these reagents find potential applications in various oxidative functionalization reactions. In recent years, the use of hypervalent iodine reagents in palladium-catalyzed transformations has been widely studied as they are strong electrophiles and powerful oxidizing agents. For instance, extensive work has been carried out in the field of C–H bond functionalization via Pd-catalysis using hypervalent iodine reagents as oxidants. In addition, now a days iodine(III) reagent have been frequently employed as arylating agents in Pd-catalyzed C‒H arylation or Heck-type cross-coupling reactions. In this review, recent advancements in the area of palladium-catalyzed oxidative cross-coupling reactions using hypervalent iodine reagents are summarized in detail.